National board of education in medicine [Merkezi̇ tip eǧi̇ti̇mi̇ sinavi (metes)] - (:unkn) unknown (My University, 2007)
As a result of new developments in the fields of medicine and of education, a report was drawn up by the Marmara University, School of Medicine, Committee of Investigation, Planning and Coordination of undergraduate medical education. This report was presented to the Council of Higher Education, Interuniversity Council.
Keywords: Assessment; Medical education; National board